2006
DOI: 10.1123/tsp.20.4.435
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptation to the Mainstream in Elite Sport: A Canadian Aboriginal Perspective

Abstract: Cultural sport psychology (CSP) is a recent attempt by researchers to better understand respondents from marginalized cultures. CSP research provides useful suggestions of how to work effectively with unique populations for coaches and sport science practitioners. This paper addresses the struggles and adaptation strategies of 23 (16 male, 7 female) elite Aboriginal Canadian athletes. National and international level athletes elicited from seven sport disciplines and three Canadian provinces were interviewed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 9 publications
4
27
0
Order By: Relevance
“…The present work is not intended as "Aboriginal research" but rather as a catalytic work with lines of questioning and research strategies that encourage voices from the intended community. Arguably, our present work provides a more reliable description of adaptation processes among adolescent sport participants from the intended community than reports that entirely reflect mainstream methodologies, such as Schinke et al (2006). Equally relevant, and in keeping with Canadian Institutes of Health Research (2007) guidelines for Aboriginal research (see also Smith, 1999), is also what might be achieved through research projects such as the present collaboration.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The present work is not intended as "Aboriginal research" but rather as a catalytic work with lines of questioning and research strategies that encourage voices from the intended community. Arguably, our present work provides a more reliable description of adaptation processes among adolescent sport participants from the intended community than reports that entirely reflect mainstream methodologies, such as Schinke et al (2006). Equally relevant, and in keeping with Canadian Institutes of Health Research (2007) guidelines for Aboriginal research (see also Smith, 1999), is also what might be achieved through research projects such as the present collaboration.…”
Section: Discussionmentioning
confidence: 89%
“…While many talented Wikwemikong athletes travel to urban centers to compete as they progress through community sport programs, many have struggled with mainstream sport encounters. The community coresearchers indicated that off-reserve sport opportunities are associated with challenges, including unfamiliar cultural traditions in and through sport practice and being confronted with racism (see also Schinke et al, 2006). Therefore, the purpose of this article was to consider the adaptation challenges and strategies of adolescent Canadian Aboriginal athletes as they travel from their community to pursue sport competitions in the mainstream culture.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Such educational training programmes have already been suggested elsewhere (Schinke et al, 2006), and the results of this study reveal the on-going importance of such interventions.…”
Section: Resultsmentioning
confidence: 80%
“…A growing body of literature -mostly conducted by North American scholars working within North America -has identified a number of important issues, such as challenges for immigrated athletes after relocation (Schinke, Yukelson, Bartolacci, Battochio, & Johnstone, 2011), their adaptation strategies (Battochio, Schinke, McGannon, Tenenbaum, & Yukelson, 2011;Schinke, Michel, Gauthier, Pickard, Danielson, Peltier, Pheasant, Enosse, & Peltier, 2006) and experiences of acculturation in new environments (Schinke & McGannon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Every athlete strives to achieve an optimal balance through coordinated effort of his/her thoughts, emotions, and behaviors. In recent years, research has focused on adaptation pathways in elite athletes which is reflected in the works of Tenenbaum et al (2003), Schinke et al (2010), Schinke et al (2006) and Tenenbaum et al (2003) reported that elite cyclists effective adaptation to daily challenges consisted of maintaining low levels of anxiety, vigor, focus and hope, flexibility within the sport context, and positive experiences of social support. Schinke et al (2010) proposed adaptation as a comprehensive intervention strategy for elite athletes where he emphasized the importance of providing additional psychological guidance and practical knowledge on how to transfer the learning from a sterile environment to a real world context.…”
Section: Social Panopticon and Adaptationsmentioning
confidence: 99%